Design of an Android-Based Public Street Lighting (LPJU) Damage Reporting Application - Lukman Reza; Nur Hamida Siregar (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
Public street lighting (LPJU) are vital facilities that assist and support community activities, especially at night. However, various problems with LPJU are still frequently encountered. Some common problems include lights going out at night, lights that are on during the day, or a specific component of the light broken. These problems are often not immediately recognized by authorities due to the lack of a fast and structured reporting system, resulting in the repair process often being delayed and having a negative impact on road users. The LPJU fault reporting system in various regions is also still manual. The purpose of this research is to design and develop an Android-based public street lighting damage reporting application to make it easier for the public to submit LPJU damage reports digitally by attaching descriptions, photos, and the location of the incident in real time. This application was developed using one of the approaches, the waterfall method. The research results show that this application can assist and facilitate the public in digitally reporting LPJU damage. Implementation of this system is expected to improve reporting efficiency, expedite follow-up on LPJU damage, and serve as a model for technology-based public service within local governments.